Autopsy interrogation of emergency medicine dispute cases: how often are clinical diagnoses incorrect?. Issue 1 (22nd July 2017) - Liu, Danyang; Gan, Rongchang; Zhang, Weidi; Wang, Wei; Saiyin, Hexige; Zeng, Wenjiao; Liu, Guoyuan
Abstract : Aims: Emergency medicine is a 'high risk' specialty. Some diseases develop suddenly and progress rapidly, and sudden unexpected deaths in the emergency department (ED) may cause medical disputes. We aimed to assess discrepancies between antemortem clinical diagnoses and postmortem autopsy findings concerning emergency medicine dispute cases and to figure out the most common major missed diagnoses. Methods: Clinical files and autopsy reports were retrospectively analysed and interpreted. Discrepancies between clinical diagnoses and autopsy diagnoses were evaluated using modified Goldman classification as major and minor discrepancy. The difference between diagnosis groups was compared with Pearson χ 2 test. Results: Of the 117 cases included in this study, 71 of cases (58 class I and 13 class II diagnostic errors) were revealed as major discrepancies (60.7%). The most common major diagnoses were cardiovascular diseases (54 cases), followed by pulmonary diseases, infectious diseases and so on. The difference of major discrepancy between the diagnoses groups was significant (p<0.001). Aortic dissection and myocardial infarction were the most common cause of death (15 cases for each disease) and the most common missed class I diagnoses (80% and 66.7% for each), higher than the average 49.6% of all class I errors of the study patients. Conclusions: High major disparities between clinical diagnoses and postmortem examinations exist in emergency medical disputes cases; acute aortic dissection and myocardial infarction are the most frequently major missed diagnoses that ED clinicians should pay special attention to in practice. This study reaffirmed the necessity and usefulness of autopsy in auditing death in EDs.